Analysis of the Participation of Micro, Small, and Medium Enterprises (MSMEs) Taxpayers in Utilizing Tax Incentives Affected by the COVID-19 Pandemic - Imam Agus Faisol; Tito IM. Rahman Hakim (Universitas Airlangga, 2021)
This study aims to assess the effectiveness of the COVID-19 tax incentives that the government has issued. It focused on Micro, Small, and Medium Enterprises (MSMEs) taxpayers to participate in COVID-19 tax incentives. Using a qualitative method, this study used in-depth interviews with 2 informants who were a tax consultant and a small-medium enterprise accountant. The findings show that the effectiveness of the COVID-19 tax incentive is still lacking, and it is in line with the participation of MSMEs that is still low in utilizing tax incentives. The low participation of MSMEs in utilizing tax incentives can be seen from the data, which shows that after 5 months of running the program, out of around 2.3 million MSMEs, only 200,000 have taken advantage of this facility. The tax consultant states that the scheme that has been implemented in mitigating the financial burden of MSMEs is not effective for the object of incentives in not substantial. The informant suggests incentives to cover value-added tax also. The government is expected to create a new and better incentive scheme. The new incentive scheme is also to provide an equilibrium of responsibility for both government and society. This paper contributes theoretically by examining new types of tax incentives, namely COVID-19 tax incentives, and helping policymakers make better tax incentive schemes in the future.